Food dishes in the Nyangahant ritual as symbols of nonverbal communication in the Salako community of Pueh Village, Lundu, Sarawak - Chelum, Alexander; Magiman, Mohamad Maulana; Chan, Siaw Leng; Kundat, Franklin Ragai (Human Resource Management Academic Research Society, 2023)
For the Salako people in Kampung Pueh, Lundu, Sarawak, the Nyangahant ritual is a very meaningful ceremony. It is an offering and prayer dedicated to Jubata, their God, for help in times of trouble, protection from threats and calamities, blessings, fertility, and wealth. The presenting of food as an offering to Jubata is an important part of the ceremony. This study used theoretical semiotics, which focuses on deciphering food's meaning in nonverbal communication, to comprehend the relevance of food symbols in the Nyangahant ceremony. As part of an anthropological study, the researcher actively participated in the ritual ceremony and conducted interviews with Tuha Adat and ritual practitioners. The research uncovered the profound meaning associated with Jubata's meals. The food on the Buis tray carried numerous connotations due to its shape, colour, and processing method. It served as an icebreaker for conversations, symbolised masculinity and traditional Salako men's cuisine, represented purity and femininity, symbolised the blessings of the upcoming harvest, fostered bonding and friendship, ensured safety, served as sacrifices, and strengthened the spiritual connection. These discoveries shed light on the deep symbolism and cultural significance of food in the Nyangahant ritual. Understanding the deeper connotations associated with food offerings allows the Salako community to strengthen their spiritual connection with Jubata while also preserving cultural customs. Furthermore, this study lays the groundwork for future research by recommending that other components of the Nyangahant ritual be investigated in order to acquire a thorough understanding of its wider cultural context and significance.